Professional competency of educational psychologist: an associative task - Juliá, María Teresa (Revista de Psicología, 2006)
The present communication raises the initial reflections of a project on academic innovation oriented towards a curriculum bases on the development of competencies for the professional psychologist of the Networl of Psychology Departments of State Universities in Chile. It examined the process of prefessional training and enhances the need to define competencies in the field of educactional psychology. After reviewing some international conceptions of professional competencies in the scope of educational psychology, it analyzes the nees to approach, as a cooperative network, the teaching necessities and the levels of education by cycles, discussing the development of a generalist or a specialized professional to give answers to the needs in the area of education.